Bioinstructive Naringin-Loaded Micelles for Guiding Stem Cell Osteodifferentiation - Lavrador, Pedro (2019)
Naringin is a naturally occurring flavanone with recognized neuroprotective, cardioprotective, anti-inflammatory, and antiosteoporotic properties. Herein, the delivery of Naringin-loaded methoxy-poly(ethylene glycol)-maleimide-thiol-poly(l-lactide) (mPEGMSPLA) diblock polymeric micelles to human adipose-derived stem cells (hASCs) with the aim to augment its pro-osteogenic effect in these cells is reported for the first time. The synthesis of the diblock copolymer is performed via Michael-type addition reaction between hydrophilic methoxy-poly(ethylene glycol)-maleimide (mPEGMAL) and hydrophobic thiol-poly(l-lactide) (PLASH) and confirmed by 1 H NMR and attenuated total reflectance Fourier transformed infrared (ATR-FTIR) spectroscopy. The resulting mPEGMSPLA copolymer self-assembles into monodispersed polymeric micelles (≈84.4 ± 2 nm) and presents a high Naringin encapsulation efficiency (87.8 ± 4%), with a sustained release profile at physiological pH. Alongside, in vitro data reveal that upon internalization into hASC 2D cultures, Naringin nanomicellar formulations attain a higher pro-osteogenic effect than that of free drug. Notably, these bioactive carriers also induce superior osteopontin expression and increase matrix mineralization in these cells over free drug administration. Overall, such findings support for the first time the use of polymeric nanomicelles for Naringin delivery into hASCs as a valid approach for modulating stem cell osteogenic differentiation.